The art of public speaking - Lucas, Stephen E.; Stob, Paul (New York McGraw Hill, 2020)
Contents: speaking and listening; speech preparation: getting started; speech preparation: organizing and outlining; presenting the speech; varieties of public speaking.
Includes bibliography and index
Keywords: Quan hệ công chúng